Kapasitas Pemerintah Desa Mekarsari Kecamatan Selaawi Dalam Mewujudkan Desa Sadar Hukum - M. A Raynanda; Nina Karlina (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2024)
Legal awareness plays an essential role in achieving legal values and goals. This awareness becomes the basis for realizing the values of legal certainty, usefulness, justice and legal objectives for general prosperity. The Regulation of the Minister of Law and Human Rights of the Republic of Indonesia stipulates that public legal awareness includes understanding and compliance with legal norms. The Legal Awareness Subdistrict/Village Program (DSH), which began in the 1980s, aims to increase residents' legal awareness through outreach by the Ministry of Law and Human Rights. In an effort to increase legal awareness, the government formed Legally Aware Families (Kadarkum) and Legally Aware Villages/Subdistricts. The Legal Awareness Family Competition, as held in several regions in Indonesia, involves the community in increasing their understanding of the law through various competitions. This research describes the capacity of the Mekarsari Village Government in realizing a Legally Aware Village, involving aspects of strategic leadership, organizational structure, human resources, financial management, infrastructure and program management. Despite facing limitations, Mekarsari Village has succeeded in creating an environment that prioritizes legal understanding and has become an example for other villages in strengthening legal awareness at the local level.